Dengue, chikungunya, and Zika virus infections imported to Paris between 2009 and 2016: Characteristics and correlation with outbreaks in the French overseas territories of Guadeloupe and Martinique. (July 2018) - Vasquez, Victor; Haddad, Elie; Perignon, Alice; Jaureguiberry, Stéphane; Brichler, Ségolène; Leparc-Goffart, Isabelle; Caumes, Eric
Abstract: Background: Dengue virus (DENV), chikungunya virus (CHIKV), and Zika virus (ZIKV) infections are rapidly expanding across countries and are being diagnosed in returned travellers who represent epidemiological sentinels. The French Territories of America (FTA) such as Guadeloupe and Martinique see high levels of tourism and have experienced three consecutive outbreaks by these viruses in the last decade. Objective: This study was performed to evaluate how ill returned travellers could have represented epidemiological sentinels for these three expanding arboviral diseases over eight consecutive years. The degree of correlation between the cases of ill returned travellers arriving at a French tertiary hospital in Paris and the three outbreaks that occurred in the FTA during the study period was estimated. Methods: All consecutive ill returned travellers diagnosed at the hospital in Paris with imported DENV, CHIKV, or ZIKV infections from January 2009 to December 2016 were included. Epidemiological and clinical variables were evaluated. Data concerning the incidence of arboviruses in the FTA, as well as the temporal relationship between the occurrence of imported cases and outbreaks in the FTA, were analyzed. Results: Overall, 320 cases of arboviral infection were reported: 216 DENV, 68 CHIKV, and 36 ZIKV. Most of the patients presented with fever and exanthema. One hundred and fifteen patients were exposed in Guadeloupe or Martinique, which were the at-risk destinations in 25% of patients with DENV, 59% of patients with CHIKV, and 58% of patients with ZIKV. The occurrence of cases diagnosed in returning travellers followed the same time pattern as the outbreaks in these areas. Conclusions: A temporal correlation was found between newly diagnosed imported cases of arboviruses and the three corresponding outbreaks that occurred in Martinique and Guadeloupe during 8 consecutive years. Thus, ill returned travellers act as epidemiological sentinels from the beginning up to the end of outbreaks occurring in touristic locations.